Diamond anvil cells using boron-doped diamond electrodes covered with undoped diamond insulating layer. (13th April 2018) - Matsumoto, Ryo; Yamashita, Aichi; Hara, Hiroshi; Irifune, Tetsuo; Adachi, Shintaro; Takeya, Hiroyuki; Takano, Yoshihiko
Abstract: Diamond anvil cells using boron-doped metallic diamond electrodes covered with undoped diamond insulating layers have been developed for electrical transport measurements under high pressure. These designed diamonds were grown on a bottom diamond anvil via a nanofabrication process combining microwave plasma-assisted chemical vapor deposition and electron beam lithography. The resistance measurements of a high-quality FeSe superconducting single crystal under high pressure were successfully demonstrated by just putting the sample and gasket on the bottom diamond anvil directly. The superconducting transition temperature of the FeSe single crystal was increased to up to 43 K by applying uniaxial-like pressure.